Selected Discourses in the Momentum of Church History According to Literature Reviews - Sudiria Hura; Marde Christian Stenly Mawikere (Peneliti.net, 2023)
This article describes the Capita Selecta of Church History Discourse According to Literature Reviews as a result of research by several historical theoloSgians. The substance of the Church History literature and the opinions of the theologians reviewed were randomly selected by the researchers. This study uses a qualitative method built by the study of literature that is relevant to the research problem. The final result of this study shows how theologians convey their perceptions of theological figures, events and works in church history which are part of the historical story of God's salvation. The final results also show that with a variety of opinions, all theologians state the benefits of learning church history for Christian ministries who are also struggling and grappling in the context of history in this world. Thus, researchers will also show that studying church history will have an impact on ministry, especially in preaching about the Person and Work of Christ as God's gift and eternal metanarration for all humans and other creations of God.